PEMBERDAYAAN PETANI GULA AREN MELALUI DIVERIFIKASI KONSENTRIS UNTUK MENINGKATKAN NILAI TAMBAH GULA AREN SEBAGAI PRODUK UNGGULAN DESA ROMBIYA TIMUR - Maksum, Maksum; Fajariyah, Robiatul Fajariyah; Fajriyah, Rini Nur Fajriyah (Abdimas IAI Ngawi, 2023)
The palm tree (Arenga pinata), which is a member of the areca nut family (Arecaceae), is a closed seed plant (Angiospermae), which means that the seeds are entirely encased in the fruit meat. In general, this plant resembles coconut trees, although palm trees have different stems from coconut trees. The trunks of coconut trees are pristine, in contrast to the filthy trunks of palm trees. Nearly every area of East Rombiya Village is covered in palm trees. The palm tree produces a sweetener known as palm sugar. East Rombiya Village, which has not been heavily farmed, is where the community processes palm sugar. Although resources from palm trees can be used in the food and beverage business, practically all sections of this plant can be utilized and have high economic value. The abundance of these resources can be used as the village's superior product. The purpose of this service is to develop palm sugar production through concentric diversification, namely the development of new products while still using the same production material, namely palm sugar. The service method is carried out through Participatory Action Research (PAR) which in this method is known as a method and strategy that can produce local leaders whose job it is to be able to continue these assisted activities after the service program ends. The results of the diversification produced by the service team are Liquid Palm Sugar and Ant Palm Sugar products. This product is a development of the production of palm sugar produced in East Rombiya Village. This product can add to the selling value of palm sugar, which is often sold at a superficial level. The diversification of palm sugar products that has been carried out can be used as a superior product in East Rombiya village to increase people's income. Keywords: Palm Sugar, concentrated Divertification, Income, Village Main Product